Formulasi Inokulan Padat Bakteri Tanah yang Menguntungkan sebagai Pengendali Nematoda pada Tanaman Kopi - Reginawanti Hindersah; Iis Nur Asyiah; Rita Harni; Dwi Suci Rahayu; Betty Natalie Fitriatin (Politeknik Negeri Lampung., 2022)
Plant Growth Promoting Rhizobacteria Pseudomonas and Bacillus are well known biofertilizer due to their ability for solubilizing inorganic phosphate and producing phytohormones in soil. However, their potential to decreased diseases incidence caused by Pratylenchus coffeae has been documented. The objective of this laboratory experiment was to formulate solid biofertilizer contained Pseudomonas diminuta and Bacillus subtilis. The laboratory experiments consisted of three-step experiment: 1) selection of the molasses-based liquid media for P. diminuta and B. subtilis growth, 2) organic liquid inoculant formulation and 3) organic carrier-based inoculant formulation. The population of both bacteria in all steps was count by serial dilution plate method with specific medium. The result verifeid that cell density of P. diminuta and B. subtilis in liquid culture with 2% molasses were higher than cell count in the culture contained 4% molasses. Bagasse-based carrier inoculated with liquid culture of mixed bacteria has higher bacterial count compared to manure-based carrier. After 90-day incubation, bagasse-based solid inoculant maintained P. diminuta and B. subtilis density up to 108 CFU/mL and the acidity of solid inculaant was about neutral. The bacterial count and acidity of solid inoculant agreed with Indonesian standard for solid biofertilizer